The Role of ChatGPT in Personal Statements for Plastic Surgery Residency Applications: Program Directors’ Perspective - Krishna A. Patel, MD; Carly J. Suriano, DO; Jeffrey E. Janis, MD, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. Personal statements are a required component of plastic surgery residency applications but can be extremely time- and labor-intensive. Artificial intelligence (AI) programs like ChatGPT can streamline personal statement writing, but their use, especially if undisclosed, can have ethical implications. This study elucidates the perspective of plastic surgery residency program directors (PDs) regarding the importance of personal statements in reviewing applicants and whether ChatGPT should be utilized. Methods:. An anonymous, 6-question multiple-choice survey was designed and administered in 3 rounds via REDCap to 120 current plastic surgery residency PDs. An additional email reminder was administered by the principal investigator. Data was collected and reported in aggregate. Results:. The survey response rate was 28.6%. Most PDs (73.5%) reported that personal statements were somewhat important in determining interviewees and the rank list; 85.3% of PDs were not confident in their ability to determine if ChatGPT was utilized. Additionally, 85.3% of residencies reported not utilizing AI-detection software, although 11.8% plan to implement one. Only 8.8% of PDs believed ChatGPT use to be ethically appropriate in all aspects of personal statement creation, whereas others believed it was only appropriate for brainstorming (11.8%), editing (14.7%), or writing (5.9%). Finally, 58.8% of PDs believed ChatGPT use to be unethical in all parts of personal statement creation. Conclusions:. The utilization of AI could have a profound impact on streamlining personal statement creation, but its use has many ethical implications. Currently, the majority of surveyed PDs feel the use of ChatGPT to be unethical in any form during personal statement writing.